TINJAUAN GEOGRAFIS DAMPAK PENGEMBANGAN EKOWISATA TERHADAP LINGKUNGAN HUTAN LINDUNG OELUAN DI DESA BIJELI KABUPATEN TIMOR TENGAH UTARA - Sanam, Maria V. I.; Samin, Mikael; Pamungkas, Bella Theo Tomi (Universitas Nusa Cendana, 2022)
One of the tourism in Bijeli Village is the Oeluan Forest tourist area. The objectives of this study to: (1) describe the physical condition of the ecotourism development of the Oeluan Forest in the research area, (2) describe the impact of ecotourism development on the environment of the Oeluan Protected Forest in the research area, ; (3) describe the government's way of dealing with the degradation of the Oeluan Forest. The type of this research is descriptive qualitative with 20 informants, selected by purposive sampling. Sources of data in the form of primary data and secondary data. Data collection methods: interviews, observations, documentation studies. Qualitative descriptive data analysis. The results of the study are as follows: (1) the development of tourism in the Oeluan Forest Area in Bijeli Village continues to increase the tourism facilities and infrastructure such as villa accommodation and other supporting facilities and infrastructure. However, with this development there are several buildings that are not considered. (2) tourism development has an impact on the environment both on the community environment and the environment of the Oeluan Forest. The impact are lack of availability of clean water and damage to vegetation due to illegal logging and neglected development which can damage the Oeluan Forest and also scattered garbage. (3) the government needs to overcome forest degradation by reforestation and prohibiting people from carrying out forest degradation and cooperate with the Bijeli community to carry out mutual cooperation.